Functional Mobility Studies in Younger Adults: Instrumented Timed Up and Go (iTUG) Test Using Inertial Devices - Kowal, Mateusz; Winiarski, Sławomir; Morgiel, Ewa; Madej, Marta; Proc, Krzysztof; Madziarski, Marcin; Wedel, Nicole; Sebastian, Agata (Journal of clinical medicine, 2025)
Functional Mobility Assessment (FMA) is a challenging task. One example of an FMA is an instrumented Timed Up and Go test (iTUG). Sensor-based interventions are more effective than traditional interventions that use clinical tests to assess a patient’s FMA. Background/Objectives: The aim of this study is to investigate the variability of selected parameters of the instrumented Time Up and Go test using inertial measurements in healthy younger adults. Methods: A total of 73 subjects participated in the study, including 37 women and 36 men. The mean age was 31 years (SD 5.5 years), the mean height [cm] was 176.2 (SD 91), and the mean BMI [kg/m2] was 26.6 (SD 3.1). The Noraxon MyoMotion Research 18 motion analysis system was used to record raw spatial data. Results: The mean total time to complete the iTUG test was 13.1 ± 1.9 s with a low coefficient of variation (CV), suggesting consistent performance between participants. The recorded spatial and temporal parameters of the gait variables, as well as the kinematic variables of the iTUG test of the studied group of healthy adults, show low variability, except for the mean double support ratio (R − L)/(R + L), which was 4.1 ± 11.0% with a CV of 271.5%, indicating a very high variability. Conclusions: The low variability observed in key parameters, such as total time and percentage of posture, suggests that the iTUG test provides reliable, objective, and reproducible measurements that can serve as normative benchmarks for healthy adults.